Voting Behavior of Batam Students in the Legislative Elections - Daniel Pasaribu; Bambang Agus Diana; Nur Hayati; Dina Fadiyah (Universitas Islam Darul Ulum Lamongan, 2022)
This study aims to analyze the voting behavior of Batam Students in the legislative elections based on voting behavior models and types. The study used qualitative research with a focus group discussion technique. The result showed that students at University are few interested in political practices and issues. The voting behavior of students is categorized as rational, critical, traditional, and pragmatism. The study found that students voted the candidate who gave them money without considering the track record, achievement, and background of the candidate.